The Role of Urgent Esophagogastroduodenoscopy in Prognosis of Acute Caustic Poisonings - Andon Chibishev; Zanina Pereska; Natasa Simonovska; Aleksandra Babulovska; Vesna Chibisheva (Academy of Medical Sciences of Bosnia and Herzegovina, 2011)
Introduction: Ingestion of corrosive substances causes severe lesions to the upper gastrointestinal tract. The aim of this paper was to present our clinical experience with the 4-grade endoscopic classification of post-corrosive injuries in prognosis of the outcome in acute caustic poisonings. Material and methods: This was a retrospective study comprising 33 patients with grade II B and III injury hospitalized at the University Clinic for Toxicology in Skopje, Republic of Macedonia in the period 2008-2009. The grade of injury was determined with urgent esophagogastroduodenoscopy performed in the first 12-24 hours. After treatment the patients were followed for a minimum of six months. Results: A total of 33 patients were analyzed. At the time of hospital admission post-corrosive injuries of grade III predominated (n=22, 66.67%) and post-corrosive injuries of grade II B (n=11, 33.33%). The most common late postcorrosive complications of the esophagus was stenosis esophagei (n=19, 57.58%). The most common post-corrosive damages of the stomach were: stenosis antropylori (n=10, 30.30%), stenosis pylori (n=6, 18.18%) and stenosis antri (n= 3, 9.09%). Conclusion: Urgent esophagogastroduodenoscopy has to be done in all acute caustic poisonings in the first 12-24 hours and they are to be classified according to Kikendall’s four-grade classification. The classification in four grades of post-corrosive injuries to the upper gastrointestinal tract might help in therapeutic approach and prognosis of the outcome
Keywords: caustic poisonings; caustic injuries; esophagogastroduodenoscopy; post-corrosive stenosis